2015
DOI: 10.1002/jemt.22471
|View full text |Cite
|
Sign up to set email alerts
|

Tract-tracing study of the extrabulbar Olfactory projections in the brain of some teleosts

Abstract: The extrabulbar olfactory projections (EBOP) is a collection of nerve fibers that originate from primary olfactory receptor neurons. These fibers penetrate into the brain, bypassing the olfactory bulbs (OBs). While the presence of an EBOP has been well established in teleosts, here we morphologically characterize the EBOP structure in four species each with a different morphological relationship of OB with the ventral telencephalic area. Tract-tracing methods (carbocyanine DiI/DIA and biocytin) were used. FMRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…This is in agreement with our data where we observed decreased neural activity in the Dp only at 18-hours post-treatment. Although we only examined cfos staining in the Dp and one other control region, extra-bulbar projections from the olfactory epithelium also project directly to regions of the brain implicated in social behaviors (such as the ventral nucleus of the ventral telencephalon, Vv, and preoptic area) [ 73 , 85 87 ] suggesting that they could also be directly affected by CoCl 2 treatment. If this is the case, cobalt chloride treatment could have even more widespread effects on neural circuits and social behaviors at multiple levels within the brain.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with our data where we observed decreased neural activity in the Dp only at 18-hours post-treatment. Although we only examined cfos staining in the Dp and one other control region, extra-bulbar projections from the olfactory epithelium also project directly to regions of the brain implicated in social behaviors (such as the ventral nucleus of the ventral telencephalon, Vv, and preoptic area) [ 73 , 85 87 ] suggesting that they could also be directly affected by CoCl 2 treatment. If this is the case, cobalt chloride treatment could have even more widespread effects on neural circuits and social behaviors at multiple levels within the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The position of the NT cells, as visualized by gonadotropin-releasing hormone (GnRH) immunohistochemistry and the type of OBs are reported to follow a particular evolutionary trend, with basal teleost species having pedunculate OBs and more peripherally displaced NT cells, whereas more derived species tend to have sessile OBs and fewer, more centrally located GnRHimmunoreactive (ir) NT cells (Parhar 2002). In addition to GnRH (Schreibman et al 1979;Oka and Ichikawa 1990;Yamamoto et al 1995), the teleost NT cells and fibres also contain FMRFamide-like compounds (Walker and Stell 1986;Ekström et al 1988;Östholm et al 1990;Rama Krishna and Subhedar 1992;Vecino and Ekström 1992;Pinelli et al 2000;Mathieu et al 2002;D'Aniello et al 2015). The presence of FMRFamide-ir NT cells in a pre-bulbar position has been reported in species with pedunculate OBs (Bonn and König 1989a;Fujii and Kobayashi 1992;Biju et al 2003), although in some other species, FMRFamide-ir NT cells have also been observed in postbulbar positions (Rama Krishna and Subhedar 1992).…”
Section: Introductionmentioning
confidence: 98%
“…The nervus terminalis complex has been described in all major groups of vertebrates (Demski, ) including lampreys and lungfishes (Von Bartheld, ), teleost fishes (D'Aniello et al, ), amphibians (McKibben, ; Muske and Moore, ; Hofmann and Meyer, ; Wirsig‐Wiechmann, ), reptiles (Johnston, ; D'Aniello et al, ), birds (Wirsig‐Wiechmann, ), and different mammalian groups (Huber and Guild, ; Larsell, ) including rodents (Bojsen‐Moller, ; Schwanzel‐Fukuda et al, ), bats (Oelschlager, ), cetaceans (Oelschlager et al, ; Ridgway et al, ), primates (Witkin, ), and humans—embryos (Bossy, ; Muller and O'Rahilly, ) and adults (Fuller and Burger, ).…”
Section: Phylogeny Of the Nervus Terminalismentioning
confidence: 99%